2020
DOI: 10.2147/ott.s255226
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long Non-Coding RNAs in Drug Resistance of Breast Cancer</p>

Abstract: Breast cancer (BC) is the most common cancer and the leading cause of death in women. Advances in early diagnosis and therapeutic strategies have decreased the mortality of BC and improved the prognosis of patients to some extent. However, the development of drug resistance has limited the success rate of systemic therapies. Long non-coding RNAs (lncRNAs) are involved in drug resistance in BC via various mechanisms, which contribute to a complex regulatory network. In this review, we summarize the latest findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 131 publications
0
9
0
Order By: Relevance
“…Downregulation of CASC2 and CDK19 increased PTX sensitivity in vitro and inhibited tumor growth in vivo [ 110 ]. Given this information, the exact mechanism of CASC2-mediated PTX resistance remains unknown but is shown to be actuated by interactions with miR-18a-5p that regulate CDK19 ([ 110 ] and reviewed in [ 111 ]). Loss of miR-17 and miR-20b confers Taxol resistance in breast cancer by enhancing expression of nuclear receptor coactivator 3 (NCOA3) [ 112 ], which is significantly upregulated in Taxol-resistant breast cancer cells.…”
Section: Taxane Resistance In Breast Cancermentioning
confidence: 99%
“…Downregulation of CASC2 and CDK19 increased PTX sensitivity in vitro and inhibited tumor growth in vivo [ 110 ]. Given this information, the exact mechanism of CASC2-mediated PTX resistance remains unknown but is shown to be actuated by interactions with miR-18a-5p that regulate CDK19 ([ 110 ] and reviewed in [ 111 ]). Loss of miR-17 and miR-20b confers Taxol resistance in breast cancer by enhancing expression of nuclear receptor coactivator 3 (NCOA3) [ 112 ], which is significantly upregulated in Taxol-resistant breast cancer cells.…”
Section: Taxane Resistance In Breast Cancermentioning
confidence: 99%
“…ncRNAs are accountable for chemoresistance (Figure 2) as they play a part in (1) moderating drug resistance related genes, (2) affecting intracellular drug concentration, (3) initiating alternative signalling pathway, (4) promoting EMT, (5) altering drug efficiency by blocking DNA damage response, (6) preventing therapeutic-induced cell death and (7) altering cell cycle [22,166,167]. In general, ncRNAs contribute to chemoresistance in different cancers [168], such as gastric cancers [169,170], pancreatic cancers [171,172], breast cancers [173,174], glioblastomas [175,176], hepatocellular carcinomas [177,178], lung cancers [179,180], leukaemias [181,182] and ovarian cancers [183,184], among others. Despite all these cancers, the following sections will focus on how ncRNAs are involved in chemoresistance arising in CRC.…”
Section: Ncrnas In Chemotherapeutic Resistancementioning
confidence: 99%
“…Currently, mounting evidences have demonstrated that lncRNAs and mRNAs played critical roles in various physiological processes, such as cell activity, gene regulation, and so on ( Fukushima and Kida, 2019 ; De Troyer et al, 2020 ; Labonté et al, 2020 ). Therefore, dissecting how lncRNAs regulate tumor progress attracts great interest from researchers ( Majidinia and Yousefi, 2020 ). In breast cancer (BRCA), high levels of BCRT1, SPRY4-IT1, RP11-19E11, and FAM83H-AS1 were associated with clinical stage and prognosis ( Giro-Perafita et al, 2020 ; Han et al, 2020 ; Liang et al, 2020 ; Song et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%